Co-delivery of dimeric camptothecin and chlorin e6 via polypeptide-based micelles for chemo-photodynamic synergistic therapy - Zhaopei Guo; Ka Hong Wong; Enze Li; Xingzhi Zhou; Di Jiang; Jiebing Gao; Meiwan Chen (BMC, 2023)
Abstract Background The integration of photodynamic therapy with a chemical drug-delivery system has displayed great potential in enhancing anticancer therapy. However, the solubility and non-specific biodistribution of both chemotherapeutic agents and photosensitizers continue to pose challenges that hinder their clinical applications. Method A polypeptide-based nanoscale drug delivery system was fabricated to address the prementioned issues. An amphiphilic polymer was formed by conjugating the photosensitizer chlorin e6 (Ce6) onto a polypeptide poly-(L-lysine)-b-polyphenylalanine (PKF) for encapsulating the model drug dimeric camptothecin (DCPT), and the nanoparticles (PCD) with high drug loading efficiency were further modified with acid-sensitive polyethylene glycol (PEG) to yield the drug delivery sytem (PPCD). Results The DCPT and Ce6 encapsulation efficiency were analyzed as 99% and 73.5%, respectively. In phosphate-buffered saline (PBS) solution at a pH of 7.4, the PEG shell improved the stability of micelles and shielded their positive charge while in the acidic tumor microenvironment, the pH-sensitive PEG layer was removed to expose the cationic nanoparticles, thus facilitating the cellular uptake of PPCD micelles. Benefiting from the enhanced cellular internalization, the amount of intracellular reactive oxygen species (ROS) treated with PCD and PPCD micelles were obviously increased. Furthermore, the enhanced anti-cancer efficacy prompted by PPCD micelles was validated through cellular and animal study. Conclusion This study presents a promising method to promote the solubility and biodistribution of both chemotherapeutic agent and photosensitizer, thereby facilitating the further application of chemo-photodynamic cancer therapy. Graphical Abstract